Rapid identification of α-glucosidase inhibitors from Poria using spectrum-effect, component knock-out, and molecular docking technique - Ma, Changyang; Lu, Jie; Ren, Mengjie; Wang, Qiuyi; Li, Changqin; Xi, Xuefeng; Liu, Zhenhua (Frontiers in Nutrition, 2023)
Instruction Poria (Poria cocos) is known for its health-promoting effects and is consumed as a food due to its potential hypoglycemic activity. However, the composition of Poria is complex, and the bioactive compounds that inhibit α-glucosidase are not clear. Methods In this study, the fingerprint of the Poria methanol extract characterized by high-performance liquid chromatography (HPLC) and the model of the corresponding spectrum-effect relationship for α-glucosidase was first established to screen the active compounds from Poria. Then, the predicted bioactive compounds were knocked out and identified using mass spectrometry. Finally, the potential binding sites and main bonds of each compound with α-glucosidase were studied using molecular docking. Results The results have shown that at least 11 compounds from Poria could inhibit α-glucosidase effectively. Moreover, eight individual compounds, i.e., poricoic acid B (P8), dehydrotumulosic acid (P9), poricoic acid A (P10), polyporenic acid C (P12), 3- epidehydrotumulosic acid (P13), dehydropachymic acid (P14), 3-O-acetyl-16α-hydroxytrametenolic acid (P21), and pachymic acid (P22), were identified, and they exhibited effective inhibitory activity against α-glucosidase. Discussion The possible inhibitory mechanism of them based on molecular docking showed that the binding sites are mainly found in the rings A, B, and C of these compounds, and C-3 C-16 and side chains of C-17, with the phenylalanine, arginine, tyrosine, histidine, and valine of α-glucosidase. The main interactions among them might be alkyl and hydrogen bonds, which theoretically verified the inhibitory activity of these compounds on α-glucosidase. The achievements of this study provided useful references for discovering bioactive compounds with hypoglycemic effects from Poria.